Rediscovering Virtual Reality in the Education of Architectural Design: The immersive simulation of spatial experiences - Antonieta Angulo (Ambiances)
The paper describes current research efforts in the College of Architecture and Planning (CAP) at Ball State University seeking to assess and make creative use of the instructional potential of immersive simulation implemented in virtual reality (VR) environments. We have conducted graduate and undergraduate design studios using the CAP VR Environment, which is a fully implemented VR environment equipped with a Head-Mounted-Display (HMD) system complete with spatial tracking capabilities. Through these implementations we have contributed to the validation of the use of the CAP VR Environment in design studios and have started to develop teaching/learning methodologies for effectively using this immersive VR environment for aiding novice students in the design of architectural spatial experiences. Assuming that only tools that allow us to simulate presence through time may effectively aid the design of spatial experiences, the CAP VR Environment has been used as such a tool for simulating and testing the effectiveness of architectural spatial experiences. The paper describes the learning outcomes in the application of the CAP VR Environment within the studio setting and the level of satisfaction of the students. It also addresses the potential for future research in the use of immersive VR tools.